Engineering structures : nonlinear analysis, optimal design and identification - Ibrahimbegović, Adnan; Brank, Boštjan (Engineering computations, 2005)
This e-book contains extended versions of the papers first presented by several invited speakers at the NATO-sponsored advanced research workshop on "Multi-physics and multi-scale computer models in non-linear analysis and optimal design of engineering structures under extreme conditions", which was held in Bled, Slovenia, from June 13 to 17, 2004. It also features a couple of papers contributed by young researchers, who all made short presentations of their research works at that meeting. The collected papers seek to present the most recent research achievements on this currently very active